1992
DOI: 10.3341/kjo.1992.6.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of fibronectin concentrations in human aqueous humor

Abstract: The concentrations of fibronectin in aqueous humor, measured by ELISA which was developed to detect fibronectin, ranged from 5 ng/ml to 100 ng/ml. Aqueous humor was aspirated from human eyes with cataracts and glaucomas using a 26 gauge needle through the peripheral cornea before making the limbal incision into the anterior chamber during surgery. The results of the study show that the average concentration and standard deviation of fibronectin was 0.136 +/- 0.192 microgram/ml in cataract eyes, and 0.962 +/- 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…In POAG aqueous, sCD44, 24 fibronectin, 43 TGF-b, 44,45 plasminogen activator inhibitor-1, 46 TIMP-2, 47 hepatocyte growth factor, 48 and VEGF 49 are increased. Prostaglandin E 2 50 and glutathione 51 levels are decreased.…”
Section: Discussionmentioning
confidence: 96%
“…In POAG aqueous, sCD44, 24 fibronectin, 43 TGF-b, 44,45 plasminogen activator inhibitor-1, 46 TIMP-2, 47 hepatocyte growth factor, 48 and VEGF 49 are increased. Prostaglandin E 2 50 and glutathione 51 levels are decreased.…”
Section: Discussionmentioning
confidence: 96%
“…[19][20][21] Various substances like growth factors, fibronectin, and so on are released into the aqueous humour after the surgery due to the breakdown of blood aqueous humour, which facilitates the proliferation and differentiation of the adhered LECs. [22][23][24] It would be worthwhile to further investigate the role of these live LECs in the incidence and severity of PCO. Our study may have clinical relevance in the context of both ACO and PCO.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of fibronectin have also been found in the JCT in some patients with POAG and in aqueous humor obtained from patients with glaucoma. Studies comparing the levels of fibronectin in aqueous humor found in patients with cataracts to that of glaucoma patients showed that the levels of fibronectin were nearly sevenfold higher in glaucomatous patients (0.136 ± 0.192 µg/mL vs. 0.962 ± 0.918 µg/mL, respectively) [14,15].…”
Section: Expression Of Fibronectin In the Trabecular Meshworkmentioning
confidence: 99%